Building Synchrotron ontology: the analysis of synchrotron control system in collaborative environment - Szota-Pachowicz, Julia (Computer Science, 2017)
This paper presents research on building a synchrotron ontology using analysis of a synchrotron control system and the aspects of collaborative ontology engineering. It includes a general description of the studied domain and the method used to develop a synchrotron domain ontology. The ontology is being created on the basis of a Solaris synchrotron control system in cooperation with the synchrotron facilities belonging to the Tango community. The first Polish synchrotron radiation facility Solaris is located at Jagiellonian University’s Third Campus in Krakow, Poland. Synchrotron is an unique source of electromagnetic radiation known as synchrotron radiation. This paper discusses the impact of the Solaris control system on the building of a synchrotron ontology. It also includes the main assumptions relating to the collaborative knowledge acquired for this domain. The synchrotron ontology will support the optimization of existing control systems and the development of a new synchrotron control system based on Tango controls or other technologies in a consistent manner. Using the same general assumptions and terms, this could be later used for integration and data sharing purposes. The synchrotron ontology can facilitate interoperation by the integration of information from different sources from one or many synchrotron control systems and integrate different parts of the controls systems that provide analogical or similar services. It can also be used to support the translation between different representations, especially regarding particular devices. Knowledge sharing and reuse is a big challenge in complex, distributed systems where the knowledge required is very specialized for different sets of functionalities or subsystems. Regarding synchrotron systems, many specialists must provide their support so the IT specialists are able to develop and maintain a control system. In this case, the synchrotron ontology can be a guideline for knowledge sharing and reuse.